Microinjection of antisense c-mos oligonucleotides prevents meiosis II in the maturing mouse egg. - O'Keefe, S J (1989)
Injection of antisense oligonucleotides was used to investigate the function of c-mos in murine oocytes. Oocytes injected with antisense c-mos oligonucleotides completed the first meiotic division but failed to initiate meiosis II. Instead, loss of c-mos function led to chromosome decondensation, reformation of a nucleus after meiosis I, and cleavage to two cells. Therefore, c-mos is required for meiosis II during murine oocyte maturation.